HUBUNGAN KOORDINASI MATA DAN TANGAN TERHADAP HASIL PUKULAN LONG SERVICE BULUTANGKIS PADA SISWA PUTRA KELAS VIII 1 SMP NEGERI 18 KOTA PEKANBARU - Sibagariang, Hesti Laila; Zainur, Zainur; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is that there are still some students when performing service is still inaccurate, serviced cock does not soar high above, especially when doing long service, as for the cause of not soaring cock because the arm muscle strength of students is not strong. Then the inaccurate results of long service carried out because there are still students who still lack the correct long service technique. The purpose of this research was to determine the relationship of eye and hand coordination to the results of a long-term bad service blow to male students of class VIII 1 Pekanbaru State Middle School 18 uri. The population and samples in this research were male students of class VIII 1 of SMP Negeri 18 Pekanbaru City, amounting to 16 people. The instrument used to collect data is eye and hand coordination tests and long-term bad service blow tests. The data analysis technique used is the r test. Based on the results of the research that has been done, it can be concluded that there is a relationship between eye and hand coordination on the results of long badminton service punches in male students of class VIII 1 in SMP Negeri 18 Kota Pekanbaru with a value of 0.566> r table 0.497.Key Words: Eye and Hand Coordination, Long Service